2011
DOI: 10.4236/ijcns.2011.411087
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of ISFET-based Device for Water Quality Monitoring

Abstract: A new configuration realizing water quality monitoring device using ISFET involving low power CMOS Integrated “Ion Sensitive Field Effect transistor (ISFET) – Operational Amplifier is presented. The study’s main focus is on simulation of power and performance analysis of ISFET device, which is used for water quality monitoring. This approach can improve calibration of device to a fairly wide range without the use of a high speed digital processor. The conventional device has a drawback of slow slew rate but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Comparing PCS with MOSFET keeping the concentration of O 2 = 1mg/l it is found that the curve resembles with the characteristic V ds /I ds curve of MOSFET keeping V gs constant [19][20][21]. Now keeping the reference voltage V gs = 0 it is observed that for different concentration levels of O 2 , different V ds /I ds curves are obtained as shown in Figure 4.…”
Section: Photo Catalysis Processmentioning
confidence: 93%
See 2 more Smart Citations
“…Comparing PCS with MOSFET keeping the concentration of O 2 = 1mg/l it is found that the curve resembles with the characteristic V ds /I ds curve of MOSFET keeping V gs constant [19][20][21]. Now keeping the reference voltage V gs = 0 it is observed that for different concentration levels of O 2 , different V ds /I ds curves are obtained as shown in Figure 4.…”
Section: Photo Catalysis Processmentioning
confidence: 93%
“…Since the two inputs occur simultaneously, so AND operator has been chosen in IF statements. R 1 : If temperature is low [10][11][12][13][14][15][16][17][18][19][20] and sensor output is low [5][6][7][8][9][10].…”
Section: Photo Catalysis Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical oxygen demand (COD) and biological oxygen demand (BOD) are the two main indices which are used globally to determine the overall quality of the water. 1 The method is very expensive, tedious and it can take several weeks to get results of the tests. One approach to solve this problem is to use several low cost sensors and try to detect correlations with the COD and BOD.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy inference engine (FIS) using inference method maps the fuzzy sets in the input space to the output space using fuzzy logic. Fusilier and defuzzifier transform the input variables to the fuzzy sets and vice versa respectively [16]. Fuzzy Rule Base implementation requires first defining the linguistic variables [9,10].…”
Section: Fuzzy Implementationsmentioning
confidence: 99%